RANCANG BANGUN APLIKASI INFORMASI SARANA KESEHATAN Di KABUPATEN KUNINGAN MENGGUNAKAN METODE LOCATION BASED SERVICE (LBS) BERBASIS ANDROID - Heru Budianto; Erik Kurniadi (Cloud Information, 2019)
Health facilities are one of the most visited places. However, in several cities, such as Kuningan regency, people still have difficulty accessing information about existing health facilities. The information needed must be complete in the form of location, type of facilities, facilities and services available. This study aims to make an application of health facilities in the Kuningan district. The design of the application uses the Rational Unified Process (RUP) system development methodology which consists of 2 dimensions, horizontal and vertical. The steps taken are inception, elaboration, construction and transition. In the inception phase, both functional and non-functional needs are identified. The elaboration phase is carried out in the design which includes designing the application architecture, use case diagrams, scenario diagrams, activities and others using the Rational Rose tool. The construction phase is carried out implementing the design into a prototype application using Android Studio tools and the Java programming language. In this phase, the process of implementing Location Based Service (LBS) technology and testing is done per unit. The transition phase is carried out the installation and testing process in the user's real condition. The results of this study are applications that are able to display information about existing health facilities. This research needs to be further developed in terms of appearance, and the use of other platforms for the use of maps.